Estimation of the Carbon Footprint of Campus Activities at the Faculty of Science and Technology, Universitas Jambi, After the Covid19 Pandemic - Windi Mulia Nofta Fani; Febri Juita Anggraini; Viareco, Hariestya (Universitas Airlangga, 2025)
Introduction: The Covid19 pandemic altered campus activity patterns, impacting energy use and transportation. As operations resumed, universities became significant contributors to carbon emissions. Without intervention, these emissions risk accelerating environmental harm. This study estimates the post-pandemic carbon footprint of campus activities to provide a foundation for emission reduction strategies at the Faculty of Science and Technology, Universitas Jambi. Methods: This quantitative descriptive study used surveys and observations at Universitas Jambi (2023) with 132 respondents via stratified sampling. Emissions were estimated using GHG Protocol scopes 1–3 and IPCC 2019 factors. Carbon-related variables were analyzed and mapped using Vensim to visualize interrelations in campus emission activities. Results and Discussion: The post-pandemic carbon footprint of campus activities at the Faculty of Science and Technology, Universitas Jambi, totaled 490.9 tons CO₂-eq in 2023. Scope 2 emissions from electricity use dominated at 78.54%, followed by Scope 3 (commuting and paper usage) at 20.29%, and Scope 1 at 1.16%. Transportation, particularly student commuting, was the largest contributor within Scope 3. Scenario simulations using Vensim revealed that carpooling and car-free day programs could reduce emissions significantly. Behavior-based interventions, including energy-saving practices and digital document usage, were identified as effective strategies to improve sustainability in daily academic operations. Conclusion: The findings support the development of targeted emission reduction strategies aligned with post-pandemic campus conditions. Its integrated approach contributes a data-driven framework for sustainable policy planning, especially for post-pandemic institutions in tropical and developing country contexts.